IMPELEMENTASI STRATEGI PEMERINTAH DESA KARANGREJO KECAMATAN ARJOSARI KABUPATEN PACITAN DALAM PENGEMBANGAN OBJEK WISATA AIR HANGAT TIRTO HUSODO - Mufti Karim Rifai; Nur Kholis; Dian Suluh Kusuma Dewi (Fakultas Keguruan dan Ilmu Pendidikan, 2020)
Tirto Husodo Hot Spring Tourism object is located 15 kilometres from Pacitan Regency or precisely in Karangrejo Village, Arjosari District, Pacitan Regency. The condition of passing vehicles passing through the lanes around these attractions is indeed practically minimal, and there is no public transportation, so tourists visiting the Tirto Husodo Hot Springs tour must use their vehicles. This research uses a qualitative approach with data collection techniques; observation, interview and documentation. The informants in this study are the village government or its ranks as well as tour managers and visitors who come to the tour. The purpose of this research is to find out the extent of the implementation of the Karangrejo Village government strategy related to the development of the Tirto Husodo Hotspring attraction, to increase attractiveness and additional income for the benefit of the Village.